2017
DOI: 10.1111/dme.13410
|View full text |Cite
|
Sign up to set email alerts
|

Serious life events and the risk of latent autoimmune diabetes in adults (LADA) and Type 2 diabetes

Abstract: Our findings indicate that experience of a serious life event, including the death of a family member, divorce or financial problems, is not associated with an increased risk of LADA, overall or in genetically susceptible individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
7
2
1
Order By: Relevance
“…Rasouli et al . found no significant association between experience of any specific serious life events and type 2 diabetes risk in older people. As for sex, however, a similar trend was not found on both sides, and we suggested that the significant associations shown in men and women varied in the types of life events experienced.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Rasouli et al . found no significant association between experience of any specific serious life events and type 2 diabetes risk in older people. As for sex, however, a similar trend was not found on both sides, and we suggested that the significant associations shown in men and women varied in the types of life events experienced.…”
Section: Discussioncontrasting
confidence: 44%
“…For example, a recent case–control study by Rasouli et al . pointed out that there was no association between experience of any specific serious life events and type 2 diabetes risk. Also, the Whitehall II study showed non‐significant associations of the number of non‐work life events with incident diabetes in both sexes.…”
Section: Introductionmentioning
confidence: 97%
“…What triggers autoimmunity besides genetic factors is not clear; Psychological stress has been linked to type 1 diabetes in children (Rewers and Ludvigsson, 2016) but no such association was seen with LADA (Rasouli et al, 2017b). In line with some findings regarding type 1 diabetes in children (Stene et al, 2003; Norris et al, 2007; Niinistö et al, 2017), fatty fish is associated with a reduced risk of LADA but unrelated to type 2 diabetes in the ESTRID Study (Löfvenborg et al, 2014).…”
Section: Etiologymentioning
confidence: 99%
“…One cross-sectional study reported a positive association between stressful life events and prevalence of undiagnosed diabetes (Mooy, de Vries, Grootenhuis, Bouter, & Heine, 2000). Two other studies [one case-control study (Rasouli et al, 2017) and another a prospective study (Kumari, Head, & Marmot, 2004)] reported weak or no association.…”
mentioning
confidence: 99%